Science and the Greater Everglades Ecosystem Restoration: An Assessment of the Critical Ecosystem Studies Initiative - National Research Council (The National Academies Press, 2003)
The report reviews a U.S. Department of the Interior research program, finding that it provides key information to support the restoration of the Florida Everglades and to better assess the impact of hydrologic change on the ecosystem. However, the program needs more funding, better management and broader distribution of its findings. The report suggests that strategic investments in Everglades research will increase the chances of reaching restoration goals while reducing overall costs.
Keywords: Environment and Environmental Studies

Progress Toward Restoring the Everglades: The Seventh Biennial Review - 2018 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure that was intended to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. Over the past two years, impressive progress has been made in planning new CERP projects, and the vision for CERP water storage is now becoming clear. Construction and completion of authorized CERP projects will likely take several decades, and at this pace of restoration, it is even more imperative that agencies anticipate and design for the Everglades of the future. This seventh biennial review assesses the progress made in meeting the goals of the CERP and provides an in-depth review of CERP monitoring, with particular emphasis on project-level monitoring and assessment. It reviews developments in research and assessment that inform restoration decision making, and identifies issues for in-depth evaluation considering new CERP program developments, policy initiatives, or improvements in scientific knowledge that have implications for restoration progress.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Fourth Biennial Review, 2012 - National Research Council (The National Academies Press, 2012)
Twelve years into the Comprehensive Everglades Restoration Project, little progress has been made in restoring the core of the remaining Everglades ecosystem; instead, most project construction so far has occurred along its periphery. To reverse ongoing ecosystem declines, it will be necessary to expedite restoration projects that target the central Everglades, and to improve both the quality and quantity of the water in the ecosystem. The new Central Everglades Planning Project offers an innovative approach to this challenge, although additional analyses are needed at the interface of water quality and water quantity to maximize restoration benefits within existing legal constraints. Progress Toward Restoring the Everglades: The Fourth Biennial Review, 2012 explains the innovative approach to expedite restoration progress and additional rigorous analyses at the interface of water quality and quantity will be essential to maximize restoration benefits.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Sixth Biennial Review - 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Everglades ecosystem is vast, stretching more than 200 miles from Orlando to Florida Bay, and Everglades National Park is but a part located at the southern end. During the 19th and 20th centuries, the historical Everglades has been reduced to half of its original size, and what remains is not the pristine ecosystem many image it to be, but one that has been highly engineered and otherwise heavily influenced, and is intensely managed by humans. Rather than slowly flowing southward in a broad river of grass, water moves through a maze of canals, levees, pump stations, and hydraulic control structures, and a substantial fraction is diverted from the natural system to meet water supply and flood control needs. The water that remains is polluted by phosphorus and other contaminants originating from agriculture and other human activities. Many components of the natural system are highly degraded and continue to degrade. Progress Toward Restoring the Everglades is the sixth biennial review of progress made in meeting the goals of the Comprehensive Everglades Restoration Plan (CERP). This complex, multibillion-dollar project to protect and restore the remaining Everglades has a 30-40 year timeline. This report assesses progress made in the various separate project components and discusses specific scientific and engineering issues that may impact further progress. According to Progress Toward Restoring the Everglades, a dedicated source of funding could provide ongoing long-term system-wide monitoring and assessment that is critical to meeting restoration objectives. This report examines the implications of knowledge gained and changes in widely accepted scientific understanding regarding pre-drainage hydrology, climate change, and the feasibility of water storage since the CERP was developed.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Fifth Biennial Review: 2014 - National Research Council (The National Academies Press, 2014)
The Everglades ecosystem is vast, stretching more than 200 miles from Orlando to Florida Bay, and Everglades National Park is but a part located at the southern end. During the 19th and 20th centuries, the historical Everglades has been reduced to half of its original size, and what remains is not the pristine ecosystem many image it to be, but one that has been highly engineered and otherwise heavily influenced, and is intensely managed by humans. Rather than slowly flowing southward in a broad river of grass, water moves through a maze of canals, levees, pump stations, and hydraulic control structures, and a substantial fraction is diverted from the natural system to meet water supply and flood control needs. The water that remains is polluted by phosphorus and other contaminants originating from agriculture and other human activities. Many components of the natural system are highly degraded and continue to degrade. Progress Toward Restoring the Everglades is the fifth biennial review of progress made in meeting the goals of the Comprehensive Everglades Restoration Plan (CERP). This complex, multibillion-dollar project to protect and restore the remaining Everglades has a 30-40 year timeline. This report assesses progress made in the various separate project components and discusses specific scientific and engineering issues that may impact further progress. According to Progress Toward Restoring the Everglades, a dedicated source of funding could provide ongoing long-term system-wide monitoring and assessment that is critical to meeting restoration objectives. The report makes recommendations for restoration activities, project management strategies, management of invasive nonnative species, and high-priority research needs.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Third Biennial Review - 2010 - National Research Council (The National Academies Press, 2010)
Although the progress of environmental restoration projects in the Florida Everglades remains slow overall, there have been improvements in the pace of restoration and in the relationship between the federal and state partners during the last two years. However, the importance of several challenges related to water quantity and quality have become clear, highlighting the difficulty in achieving restoration goals for all ecosystem components in all portions of the Everglades. Progress Toward Restoring the Everglades explores these challenges. The book stresses that rigorous scientific analyses of the tradeoffs between water quality and quantity and between the hydrologic requirements of Everglades features and species are needed to inform future prioritization and funding decisions.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The First Biennial Review, 2006 - National Research Council (The National Academies Press, 2007)
This report is the first in a congressionally mandated series of biennial evaluations of the progress being made by the Comprehensive Everglades Restoration Plan (CERP), a multibillion-dollar effort to restore historical water flows to the Everglades and return the ecosystem closer to its natural state, before it was transformed by drainage and by urban and agricultural development. The Restoration plan, which was launched in 1999 by the U.S. Army Corps of Engineers and the South Florida Water Management District, includes more than 40 major projects that are expected to be completed over the next three decades. The report finds that progress has been made in developing the scientific basis and management structures needed to support a massive effort to restore the Florida Everglades ecosystem. However, some important projects have been delayed due to several factors including budgetary restrictions and a project planning process that that can be stalled by unresolved scientific uncertainties. The report outlines an alternative approach that can help the initiative move forward even as it resolves remaining scientific uncertainties. The report calls for a boost in the rate of federal spending if the restoration of Everglades National Park and other projects are to be completed on schedule.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Second Biennial Review - 2008 - National Research Council (The National Academies Press, 2008)
This book is the second biennial evaluation of progress being made in the Comprehensive Everglades Restoration Plan (CERP), a multibillion-dollar effort to restore historical water flows to the Everglades and return the ecosystem closer to its natural state. Launched in 2000 by the U.S. Army Corps of Engineers and the South Florida Water Management District, CERP is a multiorganization planning process that includes approximately 50 major projects to be completed over the next several decades. Progress Toward Restoring the Everglades: The Second Biennial Review 2008 concludes that budgeting, planning, and procedural matters are hindering a federal and state effort to restore the Florida Everglades ecosystem, which is making only scant progress toward achieving its goals. Good science has been developed to support restoration efforts, but future progress is likely to be limited by the availability of funding and current authorization mechanisms. Despite the accomplishments that lay the foundation for CERP construction, no CERP projects have been completed to date. To begin reversing decades of decline, managers should address complex planning issues and move forward with projects that have the most potential to restore the natural ecosystem.
Keywords: Environment and Environmental Studies; Earth Sciences

Does Water Flow Influence Everglades Landscape Patterns? - National Research Council (The National Academies Press, 2003)
The report evaluates a White Paper written by restoration planners in South Florida on the role of water flow in restoration plans. The report concludes that there is strong evidence that the velocity, rate, and spatial distribution of water flow play important roles in maintaining the tree islands and other ecologically important landscape features of the Everglades.
Keywords: Earth Sciences; Environment and Environmental Studies

Florida Bay Research Programs and Their Relation to the Comprehensive Everglades Restoration Plan - National Research Council (The National Academies Press, 2002)
This report is a product of the Committee on Restoration of the Greater Everglades Ecosystem (CROGEE), which provides consensus advice to the South Florida Ecosystem Restoration Task Force. The Task Force was established in 1993 and was codified in the 1996 Water Resources Development Act (WRDA); its responsibilities include the development of a comprehensive plan for restoring, preserving and protecting the South Florida ecosystem, and the coordination of related research. The CROGEE works under the auspices of the Water Science and Technology Board and the Board on Environmental Studies and Toxicology of the National Research Council. The CROGEE's mandate includes providing the Task Force not only with scientific overview and technical assessment of the restoration activities and plans, but also providing focused advice on technical topics of importance to the restoration efforts. One such topic was to examine "the linkage between the upstream components of the greater Everglades and adjacent coastal ecosystems." This report addresses this issue by breaking it down into three major questions: What is the present state of knowledge of Florida Bay ("the Bay") on scientific issues that relate to the success of the overall CERP? What are the potential long-term effects of Everglades restoration as currently designed on the nature and condition of the Bay? What are the critical science questions that should be answered early in the restoration process to design a system that benefits not only the terrestrial and freshwater aquatic Everglades but the Bay as well? This study was inspired in part by the 2001 Florida Bay and Adjacent Marine Systems Science Conference held on April 23-26, 2001 in Key Largo, Florida. An overlapping meeting of the CROGEE was held at the same location on April 26-28, 2001. The conference was organized by the Program Management Committee (PMC) of the Florida Bay and Adjacent Marine Systems Science Program. The PMC organized the conference around five questions suggested by the Florida Bay Science Oversight Panel. These questions related to circulation, salinity patterns, and outflows of the Bay; nutrients and the nutrient budget; onset, persistence and fate of planktonic algal blooms; temporal and spatial changes in seagrasses and the hardbottom community; and recruitment, growth and survivorship of higher trophic level species. Some of these issues are discussed in the present report. However, as noted earlier, this report focuses on the subset of questions that relate to linkages between the Bay and the upstream portion of the Everglades system that arose at the 2001 Florida Bay Conference.
Keywords: Environment and Environmental Studies

Re-Engineering Water Storage in the Everglades: Risks and Opportunities - National Research Council (The National Academies Press, 2005)
The Water Science and Technology Board and the Board on Environmental Studies and Toxicology have released the seventh and final report of the Committee on Restoration of the Greater Everglades Ecosystem, which provides consensus advice to the South Florida Ecosystem Restoration Task Force on various scientific and technical topics. Human settlements and flood-control structures have significantly reduced the Everglades, which once encompassed over three million acres of slow-moving water enriched by a diverse biota. To remedy the degradation of the Everglades, a comprehensive Everglades Restoration Plan was formulated in 1999 with the goal of restoring the original hydrologic conditions of its remaining natural ecosystem. A major feature of this plan is providing enough storage capacity to meet human needs while also providing the needs of the greater Everglades ecosystem. This report reviews and evaluates not only storage options included in the Restoration Plan but also other options not considered in the Plan. Along with providing hydrologic and ecological analyses of the size, location and functioning of water storage components, the report also discusses and makes recommendations on related critical factors, such as timing of land acquisition, intermediate states of restoration, and tradeoffs among competing goals and ecosystem objectives.
Keywords: Earth Sciences; Environment and Environmental Studies

Adaptive Monitoring and Assessment for the Comprehensive Everglades Restoration Plan - National Research Council (The National Academies Press, 2003)
The report evaluates the plan to monitor and assess the condition of Florida's Everglades as restoration efforts proceed. The report finds that the plan is well grounded in scientific theory and principals of adaptive management. However, steps should be taken to ensure that information from those monitoring the ecology of the Everglades is readily available to those implementing the overall restoration effort. Also, the plan needs to place greater consideration on how population growth and land-use changes will affect the restoration effort and vice versa.
Keywords: Environment and Environmental Studies

Aquifer Storage and Recovery in the Comprehensive Everglades Restoration Plan: A Critique of the Pilot Projects and Related Plans for ASR in the Lake Okeechobee and Western Hillsboro Areas - National Research Council (The National Academies Press, 2001)
Aquifer storage and recovery (ASR) is a process by which water is recharged through wells to an aquifer and extracted for beneficial use at some later time from the same wells. ASR is proposed as a major water storage component in the Comprehensive Everglades Restoration Plan (CERP), developed jointly by the U.S. Army Corps of Engineers (USACE) and the South Florida Water Management District (SFWMD). The plan would use the Upper Floridan aquifer (UFA) to store as much as 1.7 billion gallons per day (gpd) (6.3 million m3/day) of excess surface water and shallow groundwater during wet periods for recovery during seasonal or longer-term dry periods, using about 333 wells. ASR represents about one-fifth of the total estimated cost of the CERP. Aquifer Storage and Recovery in the Comprehensive Everglades Restoration Plan examines pilot project from the perspective of adaptive assessment, i.e., the extent to which the pilot projects will contribute to process understanding that can improve design and implementation of restoration project components. This report is a critique of the pilot projects and related studies.
Keywords: Environment and Environmental Studies

Regional Issues in Aquifer Storage and Recovery for Everglades Restoration: A Review of the ASR Regional Study Project Management Plan of the Comprehensive Everglades Restoration Plan - National Research Council (The National Academies Press, 2002)
The report reviews a comprehensive research plan on Everglades restoration drafted by federal and Florida officials that assesses a central feature of the restoration: a proposal to drill more than 300 wells funneling up to 1.7 billion gallons of water a day into underground aquifers, where it would be stored and then pumped back to the surface to replenish the Everglades during dry periods. The report says that the research plan goes a long way to providing information needed to settle remaining technical questions and clearly responds to suggestions offered by scientists in Florida and in a previous report by the Research Council.
Keywords: Environment and Environmental Studies

Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. In establishing the CERP, Congress also requested that an independent scientific review be conducted on progress toward restoration with biennial reports. The National Academies' Committee on Independent Scientific Review of Everglades Restoration Progress has provided biennial reviews of restoration progress and advice on scientific and engineering issues that may impact progress since 2004. This eighth study of the series describes substantive accomplishments over the past 2 years and reviews developments in research, monitoring, and assessment that inform restoration decision making. Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 also reviews the recently developed Combined Operational Plan, which is a prerequisite for CERP progress in the central Everglades, and examines issues facing the northern and southern estuaries, including priorities for science to support restoration decision making.
Keywords: Environment and Environmental Studies; Earth Sciences